Risk Assessment in the Life Cycle of Electronic Medical Record System Development: Assasmen Risiko Dalam Siklus Hidup Pengembangan Sistem Rekam Medis Elektronik - Ningsih, Kori Puspita; Santoso, Sugeng; Purbobinuko, Zakharias Kurnia; Dewi, Tika Sari; Murdiyanto, Aris Wahyu (Procedia of Engineering and Life Science, 2025)
The Indonesian government mandated PMK 24 of 2022 concerning Medical Records as a challenge for health service facilities in Indonesia to develop Electronic Medical Records (EMR). Risk management plays an important role in every stage of the system development life cycle (SDLC). Risk assessment is the first stage in the risk management method. This research aims to explore risks in RME development in an effort to determine risk mitigation for RME development in the SDLC framework. The results of this research show the identification of risks based on hardware, software, vulnerability to technological change, vulnerability to instability in technology supply, project failure,regulatory and compliance impact. These categories of risks are outlined in the SDLC framework including the initiation, development, implementation, maintenance and disposal phases. Next, probability and impact measurements are carried out, to analyze the level of risk with low, medium and high determinants. The existence of this risk level makes it easier for stakeholders to identify appropriate controls to reduce or eliminate risks during the risk mitigation process. The output of this research is presented in the form of a risk register. The conclusion of this research shows that risks in high determinants require mitigation efforts from the aspects of regulations, infrastructure and human resources.